The Effect of Paper Puppet Media on Listening Skills for Fairy Tales in Indonesian Language Learning in Grade III Elementary School: Pengaruh Media Wayang Kertas terhadap Keterampilan Menyimak Dongeng pada Pembelajaran Bahasa Indonesia Kelas III SD - Salma, Khadijah Aufa; Wiranti, Dwiana Asih (Madrosatuna: Journal of Islamic Elementary School, 2025)
This study aims to analyze how students' listening skills to fairy tales before and after using paper puppet media, and find out how much influence paper puppet media has on listening skills to fairy tales in Grade III Indonesian language learning in elementary schools. The method used is quantitative research with a Pre-Experimental one-group pretest-posttest design. The research was conducted at SD Negeri 3 Kedungleper, involving 31 third grade students as samples. The T test results indicate that there is a significant difference before and after using paper puppet media in learning to listen to fairy tales, because the acquisition of the t value of 13.547 which is greater than the t table value of 1.69726, indicates that there is a significant effect. Paper puppets are the right learning media to help improve the skill of listening to fairy tales, this is evident from the pretest and posttest scores which have increased by 55.2%. Before this media was used, the average student pretest score was 59. After the paper puppet media was used, the average posttest score increased to 82. This increase of 55.2% means that students show a significant increase in mastering the indicators of listening to fairy tales in order to achieve the learning objectives of listening elements.